SISTEM ADMINISTRASI PAJAK PENGHASILAN (PPH) 21 PADA KOPERASI PURNA KARYA PERTAMINA (PURNAMA) CABANG MEDAN - Hariati, Hariati; Tambunan, Debora; Pasaribu, Deby Siska Oktavia (Jurnal Mahkota Bisnis (Makbis), 2025)
Pertamina Retired Work Cooperative (Purnama) is a Private Institution engaged in the field of 3 Kg LPG Agency in Medan City whose activities are distributing 3 Kg LPG to LPG Bases in Medan City and serving PT Pertamina (Persero) Retirees in terms of Annual Data Reporting and Reporting of Deaths, Ended Retirements and Widow/Widower Pension Transfers and 3 Kg LPG Bases that collaborate with this agency are Retired Employees of PT Pertamina (Persero) who want to have business activities after retirement. The object of this research is the Medan Branch of the Pertamina Retired Work Cooperative. Data collection was carried out by interviews, observations and documentation at the Medan Branch of the Pertamina Retired Work Cooperative. The collected data were evaluated using quantitative and qualitative techniques, namely analysis based on statistical calculations in the form of numbers (amounts) and analyzed in the form of descriptions which will then be systematically arranged into a Final Project. The results of the research on the hypothesis indicate that 1. The calculation and procedure for withholding Income Tax Article 21 at the Pertamina Purna Karya Cooperative, Medan Branch, as the collector of Income Tax Article 21 has not been implemented properly in accordance with the specified time and rate. The implementation of Income Tax Article 21 has not been implemented properly because the deduction of tax debt has not been made directly to the employee's payroll. So that income tax payments have not been made in accordance with the specified time.